Social Determinants of Protein-Energy Malnutrition Children under five in Kinshasa - Emile Ngoyi Muembo; Jean De Dieu Mbilia Malembu; Désiré Banga Gbanga; Lerha Lemba Kemba (Budapest International Research and Critics University, 2023)
This study focuses on the identification of the determinants of Energy Protein Malnutrition (EPM) in the peripheral area of Kinshasa. In a quantitative approach supported by a survey, anthropometric measurements (age, weight and height) are taken from 270 children under five years old. The use of the Chi-square statistical test made it possible to identify the following determinants of MPE: living in a rural environment, single-parent families and low level of education of the mother.